THE NEOPROTEROZOIC ISLAND-ARC ASSOCIATION OF THE MUKODEK GOLD-ORE FIELD, NORTHERN BAIKAL AREA - V. A. Vanin; D. P. Gladkochub; T. V. Donskaya (Геодинамика и тектонофизика, 2015)
Metamorphosed volcanic rocks of the Ushmukan suite were studied in the Mukodek gold-ore field located in the Baikal-Muya belt in the Northern Baikal area, Russia. The Ushmukan suite shows interleaving of ortoschists which compositions are widely variable. Basalt-andesite-dacite series of normal alkalinity are the substrate of the studied metavolcanic rocks. Based on the set of geochemical characteristics, it is concluded that the rocks were formed in suprasubduction geodynamic conditions corresponding to a mature island arc. The proximity of the geological locations and the similarity of the geochemical characteristics of the volcanic rocks of the Ushmukan suite and rocks of the Kelyan suite (Neoproterozoic, 823 Ma), which have similar compositions, give grounds to consider these two rock suites as age peers. Specific features of gold distribution through the Mukodek gold-ore field are analyzed. Industrial gold contents are recorded only in berezite-listvenite metasomatic rocks of the gold-quartz-sulfide formation which were formed on metavolcanic rocks of the Ushmukan suite. It is concluded that the volcanic rocks, which are specific of the island-arc setting, could be a source of gold for deposits in the Mukodek gold-ore field.